Numerical Modeling of Retaining Piles and Comparison of Results with Theoretical Relations - Abbasnejad, Alireza; Latifi Azizi, Sadra (Nexo Revista Científica, 2023)
In this research, the retaining structure of the project, which was implemented as a pile, was investigated. To investigate this research, the models were modeled in ABAQUS software and statically loaded. After analyzing the above mentioned retaining structure with the modeling soil, it is shown that, increasing the distance between the piles causes to increase the tensions and strains in the soil between them and results in more critical soil. It is also observed that the amount of tension and its distribution in the piles at a time when their distances are less is more than that of their distance between them was increased. Also, the comparison of numerical results with the results of theoretical relations indicates that the numerical values are greater than the values obtained from the theoretical relations.